Empowering maritime citizenship education: Enhancing knowledge and skills for global ocean stewardship and security - David, Muhammad; Yusuf, Rusli; Sapriya, Sapriya; Yunus, Muhammad (International Journal of Innovative Research and Scientific Studies, 2025)
Indonesia, as the world’s largest archipelagic state, holds significant maritime potential yet grapples with challenges such as climate change, pollution, and marine resource exploitation. This study evaluates the effectiveness of maritime citizenship education in enhancing the knowledge, skills, and environmental awareness of shipping polytechnic students in Aceh. Using a qualitative approach, data were gathered through in-depth interviews, participatory observations, and document analysis. The findings reveal that maritime citizenship education significantly improves students’ understanding of maritime law, sovereignty, and sustainable ocean governance. It also fosters collaborative abilities and environmental stewardship. However, the implementation still faces obstacles, including limited educational infrastructure and insufficient policy backing. Overall, the study confirms that maritime citizenship education plays a crucial role in cultivating responsible future maritime professionals who are equipped to engage in global ocean stewardship and security. The study suggests the need for deeper curricular integration to empower graduates to actively participate in marine conservation and maritime governance.